Implementation of Human Resource Management to improve the performance of youth organizations in Port Moresby - David, Emmanuel (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
This research work focuses on HRM practices in youth organizations in Port Moresby- Papua New Guinea and the resultant effect on organizational performance. Carrying out qualitative case study research with five youth organizations the study examines the recruitment; training; performance management and staff motivation strategies adopted by the youth organizations’ human resource management systems. Qualitative data were obtained by conducting 20 interviews with key informants: organizational leadership, human resource management, and programmed staffs; consulting documents. The study outcomes show that despite the presence of the practices, HRM has issues of limited resources, adopted systems, and high turnover rates that affect the implementation of the strategies. The study further establishes that absence of formal HR systems, and difficulties in maintaining motivated workforce, affect the organizational performance. In relation to the HRM literature, these findings add to the limited research that has been done on practicing HRM in non-profit youth organizations with specific focus on the developing nations. Aid from the study is that HRM should be a context that requires the identification of suitable strategies that may offset the scarcity of resources and lead to enhanced organizational performance.